Dialogue summary: Enhancing programs and policies for injured workers with chronic pain in Canada - Moat, KA; Dass, R; Whitelaw, H (My University, 2024)
A thematic summary of what was learned from the stakeholder dialogue on enhancing programs and policies for injured workers with chronic pain in Canada, about the problem (and its causes), elements of a potentially comprehensive approach for addressing it, key implementation considerations, and possible next steps.
Keywords: injured workers; chronic pain; Canada